Busca e uso da informação na autogestão corporal - Ana Maria da Silva Rodrigues (2004)
The society nowadays presents its own particularities and dynamics. It is a post-traditional society, not subjected to tradition anymore, where individuals acts are oriented and held under their own guidance. It is a risk society, because at the same time it offers choiceauthonomy, it turns individuals responsible for the the risks they may bring. It is a time where the social actions are often reformulated based on information, given the greater ammount and ubiquity of these information. Then the body, as the concreteness that identify and distinguish individuals, become the center of the decisions; it is explored and experienced,emitting information in the social relationships and promoting self-perception conditions. This thesis had investigated bodyworker´s search strategies and use of the information for the body self-management, aiming to (a) analise the influence of the information broadcasted from media, expert systems, and bodybuilding specialists; by the individuals themselves,corporal beauty patterns and how these information influence the body self-management; (b) explore the social environment of the gyms as a place that allows socialization and selfmanagement, and pave the ways for self-identity building. For the data gathering, besides participant observation technics, it was used semi-structured interviews with 14 participants from a Gym in Teresina (PI). The results shows that body activities in a social institution like the gym are answers to the individual, diving in an uncertainty environment, uncertainties that are a characteristic of the contemporaneity; it promotes presential interactionoportunities with fellows with common interests and lead to the self awareness through the information gathered in formal and informal sources, and those emitted by the bodies itselves. It is understood that information happens through a communication proccess and meaning aquisition by the individual, with the potential to turn into knowledge to guide thepersonal decisions. Nevertheless, the body information search by the interviewed individuals has shown circunstantial and sometimes casual, in spite of the importance that they credit to the information. The media influence as information sourcees acts in an confusing way, and its credibility is attached to the expert support. The media broadcasts some men and women body standards that acts as references, because each one of the interviewd has shownknowledge about the limits and potentiality of their own bodies. It was verified that enduring in bodybuilding activities is a consequence of the aesthetic results, that bring some health, well being and selfsteem, continuously evaluated and confronted, showing reflexivity. It seems that in gym academies the self identity is a fact. It was observed that bodyworkingactivities outstands the activity itself, giving some clues that indicates more wider aspects of the individuals life, that can be considered as self-identity constituints.